2022
DOI: 10.1136/wjps-2021-000271
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in children with acute fulminant myocarditis receiving venoarterial extracorporeal membrane oxygenation

Abstract: BackgroundPediatric acute fulminant myocarditis (AFM) is a very dangerous disease that may lead to acute heart failure or even sudden death. Previous reports have identified some prognostic factors in adult AFM; however, there is no such research on children with AFM on venoarterial extracorporeal membrane oxygenation (VA-ECMO). This study aimed to find relevant prognostic factors for predicting adverse clinical outcomes.MethodsA retrospective analysis was performed in an affiliated university children’s hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…We further excluded 42 studies after full‐text evaluation, because they did not meet inclusion criteria. Eventually, 28 studies 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 were amenable to meta‐analysis (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We further excluded 42 studies after full‐text evaluation, because they did not meet inclusion criteria. Eventually, 28 studies 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 were amenable to meta‐analysis (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our meta‐analysis, applying a random‐effects model, the pooled short‐term mortality (28 studies,1736 patients) was 45.6% (95% CI, 38.7%–52.4%) (Figure 2 ). 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 There was no evidence for publication bias because of the funnel plot appearing visually symmetrical (Figure 3 ), and the Egger test suggesting insignificant difference for our primary outcome of interest ( P egger =0.23). The sensitivity analysis performed by excluding the studies with a Joanna Briggs Institute score <8, showed that the pooled short‐term mortality was 46.2% (95% CI, 39.0%–53.4%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations